Fiber-reinforced technology in multidisciplinary chairside approaches - Arhun Neslihan; Arman Ayca (Wolters Kluwer Medknow Publications, 2008)
There is an increasing demand to improve dentofacial esthetics in the adult population. This demand usually requires a close collaboration within the various disciplines of dentistry and the patient at every stage of the therapy. The materials and techniques used by these interdisciplinary clinicians must be conservative and minimally invasive. Fiber-reinforced composite technology offers such solutions for chairside applications. This case report presents two cases where fiber-reinforced ribbon and composite complex was used in a multidisciplinary approach to improve esthetics.